Is asymmetric upper trapezius muscle activation during work associated with neck pain? A cross-sectional and longitudinal analysis - Markus Koch; Xuelong Fan; Lars Louis Andersen; Markus Due Jacobsen; Mikael Forsman; Gisela Sjøgaard; Karen Søgaard; Christoph Anders; Sanna Grydeland; Lars-Kristian Lunde (PLoS ONE, 2026)
Objectives Previous studies have linked activity in the upper trapezius muscle with neck pain. However, no studies have examined whether asymmetric activation of these muscles during the working day is associated with neck pain. This study aimed to investigate this relationship. Methods Seven research institutes provided data on bilateral upper trapezius muscle activity on one working day, along with corresponding questionnaire data on cross-sectional (n = 530) and longitudinal (n = 256) neck pain intensity. The asymmetry, defined as the activity difference between the two upper trapezius muscles, was calculated as an average across the entire workday and within various intensity levels in relation to maximum voluntary isometric contraction (MVIC). Unadjusted and adjusted linear regression analyses were executed to examine the association between asymmetric muscle activation and neck pain intensity. Results In cross-sectional analyses, asymmetry in the levels 0–0.05 and 0.05–2%MVIC was significantly positively associated with neck pain intensity in both unadjusted and adjusted analyses. Asymmetry in the levels of 4–6, 6–8 and 8–10%MVIC was significantly negatively associated with neck pain in unadjusted analyses. In longitudinal analyses, significant positive associations were found for asymmetry in level 0–0.05%MVIC and negative associations for asymmetry in levels > 20%MVIC. Conclusion While asymmetry in the very low levels of muscle activity may be associated with higher neck pain intensity, asymmetry in the higher levels of muscle activity was negatively associated with neck pain intensity. However, the explained variance of the models was small, and the results should therefore be interpreted with caution. The findings suggest that work conditions facilitating simultaneous relaxation during breaks and balanced activation of both muscles during static activities may be relevant for neck pain prevention, though further research is needed to establish causality.